Experimental study on ferritic stainless steel trapezoidal decks for composite slabs in construction stage. (January 2019) - Arrayago, I.; Real, E.; Mirambell, E.; Marimon, F.; Ferrer, M.
Abstract: The use of composite floor slabs is well established and provides an opportunity to promote the use of visually exposed composite slabs. Stainless steels, with the combination of good mechanical properties and excellent corrosion resistance, are key to this strategy, specially ferritic stainless steels, whose price is lower and more stable than that corresponding to the more widely used austenitic grades, due to their low nickel content whilst still maintaining good mechanical properties and aesthetic appeal. In addition, the emissivity of these grades contributes to lowering the heating and cooling requirements of buildings, reducing the costs associated to maintenance. Generally used as cold-formed members with high resistance-to-weight ratios, stainless steel decks are slender and highly sensitive to buckling phenomena and so the study of the structural performance of composite slabs using ferritic stainless steel decking is required due to the complex nonlinear behaviour of stainless steels, which is very different from that exhibited by carbon steel. Thus, this paper presents a comprehensive experimental programme on ferritic stainless steel trapezoidal decks for composite slabs under several structural configurations occurring during construction stage: simply supported decks under positive and negative bending moment, continuous decks and internal and end support tests. All the experimental results have been compared with the predicted ultimate loads in EN 1993-1-4, which remits to EN 1993-1-3 for carbon steel, and also with some previous tests on galvanized carbon steel decks. The paper concludes that EN 1993-1-3 provisions are applicable to ferritic stainless steels. Highlights: Experimental programme on ferritic stainless steel trapezoidal decks for composite slabs is presented. Simply supported, continuous deck, internal and end support tests are reported. The assessment of EN 1993-1-3 expressions for ferritic stainless steel decks is conducted. Tests results are compared to similar experiments on carbon steel decks.